ANALISIS TINGKAT KERENTANAN BENCANA (STUDI KASUS: KAWASAN CAGAR BUDAYA CANDI MUARA JAMBI) - Maryani, Enok; Sipayung, Wendy Yudistira; Somantri, Lili; Setiawan, Iwan; Nandi, Nandi; Sitepu, Surianto (Jurnal Master Pariwisata (JUMPA), 2023)
Cagar Budaya Candi Muara Jambi Area is one of the national heritages which is a cultural heritage in Jambi Province with an area of 3,981 hectares. The located of Kawasan Cagar Budaya Candi Muara Jambi is at the estuary of the Batanghari River which poses a threat to the flood disaster of the Batanghari River in every rainy season. The study aims to maaping the level of vulnerability and to analyse the level of disaster vulnerability by reducing the impact of losses and the impact of disaster due to the Batanghari River flood disaster in the Kawasan Cagara Budaya Candi Muara Jambi. Determination of the level of disaster vulnerability through four parameters of vulnerability, they are social vulnerability, economic vulnerability, physical vulnerability, and environmental vulnerability. The approach of the studi is GIS approach with an analysis of the level disaster vulnerability is using overlay, scoring, and weighting techniques. The results of the study is disaster vulnerability level of flood disaster in Kawasan Cagar Budaya Candi Muara Jambi is at medium level of disaster vulnerability. Keywords: flood disaster; watersheds; vulnerability disaster.